2014
DOI: 10.1515/jip-2013-0068
|View full text |Cite
|
Sign up to set email alerts
|

Regularization of linear inverse problems with total generalized variation

Abstract: The regularization properties of the total generalized variation (TGV) functional for the solution of linear inverse problems by means of Tikhonov regularization are studied. Considering the associated minimization problem for general symmetric tensor fields, the well-posedness is established in the space of symmetric tensor fields of bounded deformation, a generalization of the space of functions of bounded variation. Convergence for vanishing noise level is shown in a multiple regularization parameter framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 27 publications
1
133
0
Order By: Relevance
“…The remaining assertions follow immediately from the equivalence of ICTV n β to TGV k α with k = md(β), α ∈ R k + , and the corresponding assertions on TGV k α as in [10]. Below, for any orthogonal matrix O ∈ R d×d and ξ ∈ Sym k (R d ), k ∈ N, we define the right multiplication ξO ∈ Sym k (R d ) by…”
Section: Properties Of Ictvmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining assertions follow immediately from the equivalence of ICTV n β to TGV k α with k = md(β), α ∈ R k + , and the corresponding assertions on TGV k α as in [10]. Below, for any orthogonal matrix O ∈ R d×d and ξ ∈ Sym k (R d ), k ∈ N, we define the right multiplication ξO ∈ Sym k (R d ) by…”
Section: Properties Of Ictvmentioning
confidence: 99%
“…In [10] it has been shown that TGV k β , with | · | β i = α −1 i | · |, can equivalently be written as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of such a model allows to get rid of the staircasing effect that appears with the ROF model in denoising processes. To achieve this goal, Bredies et al [15][16][17] have recently introduced a second-order generalized total variation definition that is a nice compromise/mixture between the firstand second-order derivatives. It is, in some sense, an extension of the inf-convolution (we recall the definition later) of the first-and second-order derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Variational methods were rapidly applied along with data fidelity terms Ψ. The use of differential operators D k of various orders k 2 in the prior Φ has been recently investigated, see, e.g., [22,23]. More details on variational methods for image processing can be found in several textbooks like [3,5,91].…”
Section: F(u V) = − Ln π(V|u) − Ln π(U)mentioning
confidence: 99%